Diosgenin: Recent Highlights on Pharmacology and Analytical Methodology - Mafalda Jesus; Ana P. J. Martins; Eugenia Gallardo; Samuel Silvestre (Journal of Analytical Methods in Chemistry)
Diosgenin, a steroidal sapogenin, occurs abundantly in plants such as Dioscorea alata, Smilax China, and Trigonella foenum graecum. This bioactive phytochemical not only is used as an important starting material for the preparation of several steroidal drugs in the pharmaceutical industry, but has revealed also high potential and interest in the treatment of various types of disorders such as cancer, hypercholesterolemia, inflammation, and several types of infections. Due to its pharmacological and industrial importance, several extraction and analytical procedures have been developed and applied over the years to isolate, detect, and quantify diosgenin, not only in its natural sources and pharmaceutical compositions, but also in animal matrices for pharmacodynamic, pharmacokinetic, and toxicological studies. Within these, HPLC technique coupled to different detectors is the most commonly analytical procedure described for this compound. However, other alternative methods were also published. Thus, the present review aims to provide collective information on the most recent pharmacological data on diosgenin and on the most relevant analytical techniques used to isolate, detect, and quantify this compound as well.